The modulation of ion channels in cancer chemo-resistance - Zhao, Jiayu; Li, Mei; Xu, Jiao; Cheng, Wei (Frontiers in Oncology, 2022)
Ion channels modulate the flow of ions into and out of a cell or intracellular organelle, leading to generation of electrical or chemical signals and regulating ion homeostasis. The abundance of ion channels in the plasma and intracellular membranes are subject to physiological and pathological regulations. Abnormal and dysregulated expressions of many ion channels are found to be linked to cancer and cancer chemo-resistance. Here, we will summarize ion channels distribution in multiple tumors. And the involvement of ion channels in cancer chemo-resistance will be highlighted.